Standard characteristics of the Jacek Leluk Intelligence Test according to the three-parameter model among middle school students - Dr. Heba Muhammad Ali Abd (Journal of College of Education, 2024)
The current research aims to extract the standard characteristics of the mental ability test prepared by the author (jacek leluk) for the middle school stage using the three-parameter model. To achieve this goal, the researcher followed scientific steps in extracting the standard characteristics of the test, starting with translating the test items and instructions from English to Arabic. Then, it was re-translated from Arabic to English, taking into account the accuracy and comprehensiveness of all the ideas present in the test. The researcher took into account the amendments that were made to the translation when it was presented to the translation experts. Then, she presented the test instructions and paragraphs to an expert specializing in the Arabic language, and after taking his comments It was presented to the arbitrating experts in the educational and psychological sciences, to ensure the availability of appropriate characteristics for it and its alternatives in terms of form and content, and the researcher took their opinions, and all the test items were considered logically valid to measure what they were designed to measure. To ensure the clarity of the test instructions and items and to determine the performance time, the application The test was conducted on a reconnaissance sample of (60) male and female students other than the statistical analysis sample. It appeared that the test instructions and paragraphs were clear, and the performance time was set at (45) minutes. The test was applied to a sample of (1,000) male and female students (Wasit Governorate). They were selected using a multi-stage random sampling method, and the researcher relied on a three-teacher model, which is one of the models of the item response theory to analyze the test items. To verify the model’s assumptions, the researcher followed the following: The statistical analysis according to the item response theory was done through the researcher relying on a tripartite model. The teacher as one of the models of item response theory in analyzing the items of the mental ability test, as calculated by the Biolog program (Bilog-m3). To achieve the model’s assumptions, the researcher followed the following